Przestrzeń pozasceniczna w „Fenicjankach” eurypidesa i jej funkcja dramaturgiczna - Czerwińska, Jadwiga (Collectanea Philologica, 2025)
Euripides’ The Phoenician Women belongs to the category of tragedies in which the offstage space – that is, events occurring beyond the immediate visual perception of the audience – plays a significant role. These events are crucial not only for the development of the drama but also for the poetic vision conveyed by the author through them. In depicting actions that, due to their nature, could not be shown ad oculos to the spectators, Euripides employs messengers’ speeches and dialogues among the dramatis personae, thereby drawing upon the audience’s imaginative faculty and utilizing the commentary layer of the drama. Thus, the spectator participates in the expansion of the tragic stage space, conjuring in the mind’s eye poetic images of the offstage world. Given the rich textual representation of offstage space in The Phoenician Women, the present analysis will focus on two scenes: the teichoscopy (lines 98-201) and the first part of the Messenger’s speech to Jocasta (lines 1090-1138), which alludes to the former.